2022
DOI: 10.21608/ejar.2022.155457.1263
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing growing quail diets with silymarin and curcumin to improve productive performance and antioxidant status and alleviate aflatoxin b1 adverse effects during the summer season

Abstract: The current experiment was carried out to test the ability of supplementing growing quail diet with silymarin and curcumin as natural antioxidants to improve antioxidant status of growing Japanese quail and alleviate aflatoxin B1 adverse effects during the summer season. Three levels each of curcumin and silymarin (zero, 250mg and 500mg/kg diet) were combined to compose 9 experimental diets and the diet that contains zero levels from each natural antioxidant acted as a control basal diet. Three hundred and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In quails, a dose of 1000-2000 mg/kg/diet of SIL (analytical composition unknown) plus AFs (2.2 mg/kg/diet, as AFB 1 : 68.19%, AFB 2 : 4.57%, AFG 1 : 24.96%, AFG 2 : 2.28%), showing an increase in BWG correlated with a good FCR, with a minor rate of mortality compared to the poisoned group, and control group [63]. Similarly, Youssef and colleagues [64] evidenced an improvement, increasing supplementation levels of SIL to 500 mg/kg/diet plus AFB 1 (19 ppb/kg/diet), in BW and BWG but not in FCR. Even in quails, the addition of 500 g/ton/diet of SIL in a diet contaminated with AFs (1500 µg/kg/diet, as AFB 1 : 84.64%; AFB 2 : 4.28%; AFG 1 : 11.07%), for 60 days of treatment, demonstrated that SIL was not able to mitigate the negative effects of AFs.…”
Section: Influence Of Sil On Immunological Parameters In Myt-poisoned...mentioning
confidence: 84%
See 3 more Smart Citations
“…In quails, a dose of 1000-2000 mg/kg/diet of SIL (analytical composition unknown) plus AFs (2.2 mg/kg/diet, as AFB 1 : 68.19%, AFB 2 : 4.57%, AFG 1 : 24.96%, AFG 2 : 2.28%), showing an increase in BWG correlated with a good FCR, with a minor rate of mortality compared to the poisoned group, and control group [63]. Similarly, Youssef and colleagues [64] evidenced an improvement, increasing supplementation levels of SIL to 500 mg/kg/diet plus AFB 1 (19 ppb/kg/diet), in BW and BWG but not in FCR. Even in quails, the addition of 500 g/ton/diet of SIL in a diet contaminated with AFs (1500 µg/kg/diet, as AFB 1 : 84.64%; AFB 2 : 4.28%; AFG 1 : 11.07%), for 60 days of treatment, demonstrated that SIL was not able to mitigate the negative effects of AFs.…”
Section: Influence Of Sil On Immunological Parameters In Myt-poisoned...mentioning
confidence: 84%
“…In comparison, they decreased significantly in groups treated with lycopene (100 mg/kg/diet) plus SIL (SIL 80%, analytical composition not reported) at a dose of 600 mg/kg-BW, as well as creatinine, with an associated increase of serum total protein and albumin. These latter parameters were altered in quail treated with AFB 1 at a dose of 1500 µg/kg/diet [62], but not when fed with 250-500 mg/kg/diet of SIL [64]. No changes were observed in biochemical parameters in quail treated for 60 days with beta-glucans (1 kg/ton/diet) or SIL (500 g/ton/diet) plus AFB 1 [62].…”
Section: Sil Effects On Serum-biochemical Parameters On Myt-poisoned ...mentioning
confidence: 88%
See 2 more Smart Citations
“…Silymarin is an antimicrobial, an anticancer and has a protect effects on cardiovascular, neuro system and skin (Wang et al, 2020). Silymarin has an antioxidant activity when inserted in quail diets and improve growth performance (Youssef et al, 2022). Similarly, adding curcumin to quail diet improved feed conversion and enhanced egg production when quail exposed to thermal stress, besides egg quality improved (Marchiori, et al, 2019).…”
Section: Unitedmentioning
confidence: 99%